2018
DOI: 10.3389/fmicb.2018.00660
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics of Smut Pathogens: Insights From Orphans and Positively Selected Genes Into Host Specialization

Abstract: Host specialization is a key evolutionary process for the diversification and emergence of new pathogens. However, the molecular determinants of host range are poorly understood. Smut fungi are biotrophic pathogens that have distinct and narrow host ranges based on largely unknown genetic determinants. Hence, we aimed to expand comparative genomics analyses of smut fungi by including more species infecting different hosts and to define orphans and positively selected genes to gain further insights into the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 126 publications
(143 reference statements)
2
29
0
1
Order By: Relevance
“…Benevenuto et al . 39 compared the genomics of ten smut fungi isolated from maize, barley, sugarcane, wheat, oats, Zizania latifolia (Manchurian rice), Echinochloa colona (a wild grass), Persicaria sp. (a wild dicot plant), oats, and wheat; they showed that host domestication did not play a dominant role in shaping the evolution of smuts; however, the diversification and gain or loss of effector genes are probably the most important determinants of host specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Benevenuto et al . 39 compared the genomics of ten smut fungi isolated from maize, barley, sugarcane, wheat, oats, Zizania latifolia (Manchurian rice), Echinochloa colona (a wild grass), Persicaria sp. (a wild dicot plant), oats, and wheat; they showed that host domestication did not play a dominant role in shaping the evolution of smuts; however, the diversification and gain or loss of effector genes are probably the most important determinants of host specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Once the effector targets have been identified, some of these could be exploited for resistance breeding (Gawehns et al, 2013). Also in this respect functional genomics can be deployed because effectors usually contain common regulatory cis-elements in their promoters or secretion signals in their peptides, which can be searched in pathogen genomes to identify candidate genes for further analysis (Zwiesler-Vollick et al, 2002;Benevenuto et al, 2018;Ai et al, 2020). Altering the host targets to prevent manipulation by pathogen effectors will impair compatibility and render the plant more resistant.…”
Section: Pipeline For Target Gene Identification In Resistance Breedingmentioning
confidence: 99%
“…However, prominent intron loss has also occurred in Ustilaginomycotina (Kämper et al 2006;Stajich et al 2007) . Many of these smuts and allies have evolved into plant pathogens and evolved a yeast state as part of their life cycle (Rush and Aime 2013;Wang et al 2015;Benevenuto et al 2018;Kijpornyongpan et al 2018) .…”
Section: Widespread Intron Loss In the Fungal Kingdommentioning
confidence: 99%